Elderly Patient Safety Management Using Peer to Peer Safety Companion (P2PSC) Intervention - Iswati Iswati; Ana Zakiyah (Adi Husada Nursing Journal, 2025)
Adverse events, particularly falls and medication errors, remain a significant challenge in elderly patient care at home. The Peer to Peer Safety Companion (P2PSC) intervention leverages peer support to enhance patient engagement and safety vigilance. This study aimed to evaluate the effectiveness of P2PSC in reducing fall risk and improving medication adherence among elderly patients at home. A quasi-experimental one-group pretest-posttest design involved 56 elderly participants receiving P2PSC support for 4 days over 2 weeks. Data analysis revealed significant reductions in fall incidents (p=0.001) and improvements in medication adherence (p=0.001). Mean fall risk scores decreased from 12.5 to 9.2, while medication adherence scores increased from 72.5 to 81.3. The P2PSC intervention effectively enhances safety management for elderly patients and is recommended as a supplementary standard in geriatric care management at home.